EVALUATION OF POTENTIAL ANTIMICROBIAL ACTIVITY OF SYNTHETIC FLAVONOIDS - Bhixavatimath, Prabhulingayya S; Maniyar, Yasmeen; Naikawadi, Akram; Vijayakumar D (Journal of Biomedical and Pharmaceutical Research, 2021)
Introduction: In recent times, most of the currently available antimicrobial agents have developed resistance. Extensive pharmacological activities including bactericidal and bacteriostatic nature of flavonoids, made them as priority agents in this aspect of research study. Synthetic flavonoids such as hydroxy thiophen derivatives were considered to evaluate for antimicrobial activity in this study.  Objective: The present study involves the analysis for antimicrobial activity of thiophen substituted synthetic flavonoids.Methods: Claisen-Schmidt method of condensation fallowed by oxidative cyclization reactions from substituted hydroxyacetophenone with aromatic aldehydes were used to synthesize the various analogues of flavonoid compounds. Then these compounds after their FTIR, 1H NMR, MS spectral characterization and elemental analysis, were screened for in vitro antibacterial and antifungal activity by using disc diffusion method followed by determining their respective zone of inhibitions.Results: All the synthesized test flavonoid compounds exhibited the good antibacterial and antifungal  spectrum activity over B. subtilis, S. aureus, E. coli and P. aeurugenosa bacteria and Candida albicans and Aspergillus niger fungal microbes. However compounds such as F1, F2 and F4 showed moderately significant antibacterial activity against P. aerugenosa organism than the other test compounds and the same F1 and F2 test compounds exhibited significant antifungal activity at100µg concentration.Conclusion:  The present study demonstrated that the novel thiophen substituted flavonoids (F1, F2, F3 and F4 ) found to have promising antimicrobial and antifungal activity which needs to be confirmed by in vivo studies.